Designing multimodal composition activities to support integrated primary programming and storytelling - Whyte, Robert (2021)
A broad interest in embedding computer science (or computing) education in formal learning contexts has resulted in a proliferation of research on the teaching and learning of programming. Much of this research has focused on supporting learning in science, engineering, and mathematics (or STEM), as computing education is seen to promote problem solving (Wing, 2006), with much less work conducted in non-STEM (e.g., literacy) content areas. This thesis adds to this latter by investigating the potential for integrated computing and literacy education by proposing multimodal composition (MMC) as a framing device for supporting children’s storytelling and programming practices.